2009
DOI: 10.1111/j.1439-0272.1994.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghloroquine excretion in semen following antimalarial-drug administration

Abstract: The study described here was carried out to establish whether or not chloroquine was excreted in semen. Chloroquine was assayed in the semen of eight male volunteers (aged between 19 and 45 years) by a fluorimetric method before and after taking a total dose of 1.500 mg chloroquine base corresponding to the accepted dosage of the drug in malarial chemotherapy. Mean preand post-drug administration levels of 0.7 f 0.2 p~ and 5.7 f 0.6 p~ were obtained respectively, indicating a significant excretion of chloroqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Four studies that included data from 37 healthy men were identified. One study reported sperm quality parameters and three studies evaluated the ability of chloroquine to cross the blood-testis barrier ( Ette et al , 1988 ; Adeeko and Dada, 1994 ; Hargreaves et al , 1998 ; Ejebe et al , 2008 ). As it is the case for other human tissues and fluids, chloroquine can be found on seminal plasma even after long-term withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies that included data from 37 healthy men were identified. One study reported sperm quality parameters and three studies evaluated the ability of chloroquine to cross the blood-testis barrier ( Ette et al , 1988 ; Adeeko and Dada, 1994 ; Hargreaves et al , 1998 ; Ejebe et al , 2008 ). As it is the case for other human tissues and fluids, chloroquine can be found on seminal plasma even after long-term withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…The yellow discoloration of semen was an unexpected finding and appears to be an isolated observation attributable to one or more colored metabolites. The presence of drug or drug metabolites in semen is not unusual; caffeine ( 18 ), aspirin ( 19 , 20 ), and chloroquine ( 21 , 22 ) are some examples of compounds for which this is reported. Where samples were provided, we found no azospermia, diminished motility, or clinically significant abnormality in semen.…”
Section: Discussionmentioning
confidence: 99%
“…It can theoretically inhibit the acrosome reaction of spermatozoa and reduce their fertilization capacity. However, the data in the literature that describe the impact of Chloroquine on male fertility are still insufficient (Okanlawon et al ., ; Adeeko & Dada, ; Hargreaves et al ., ; Østensen et al ., ; Grunewald et al ., ; Millsop et al ., ).…”
Section: Resultsmentioning
confidence: 99%